2023
DOI: 10.21203/rs.3.rs-3139798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced immune ageing associated with increasing COVID-19 disease severity

Abstract: Background The striking increase in COVID-19 severity in older adults provides a clear example of immunesenescence, the age-related remodelling of the immune system. To better characterise the association between convalescent immunesenescence and acute disease severity, we determined the immune phenotype of COVID-19 survivors and non-infected controls. Results We performed detailed immune phenotyping of peripheral blood mononuclear cells isolated from 103 COVID-19 survivors 3–5 months post recovery who were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Single-cell RNA sequencing in both young and elderly animals has shown that aging lead to significant remodeling and phenotypic reprogramming of T-cell landscapes [42]. The COVID-19 pandemic had underscored that the accelerated immune ageing was associated with respiratory disease progression [43]. PD-1 had been recognized as a marker of immune cell aging, which drived systemic aging [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing in both young and elderly animals has shown that aging lead to significant remodeling and phenotypic reprogramming of T-cell landscapes [42]. The COVID-19 pandemic had underscored that the accelerated immune ageing was associated with respiratory disease progression [43]. PD-1 had been recognized as a marker of immune cell aging, which drived systemic aging [44,45].…”
Section: Discussionmentioning
confidence: 99%